From the line equation, we can deduce
![x=-4y](https://tex.z-dn.net/?f=x%3D-4y)
This implies that any point on the line can be written as
![(-4y,y),\quad y \in \mathbb{R}](https://tex.z-dn.net/?f=%28-4y%2Cy%29%2C%5Cquad%20y%20%5Cin%20%5Cmathbb%7BR%7D)
So, given any two points
![A=(-4y_1,y_1),\quad B=(-4y_2,y_2)](https://tex.z-dn.net/?f=A%3D%28-4y_1%2Cy_1%29%2C%5Cquad%20B%3D%28-4y_2%2Cy_2%29)
their distance will be
![AB=\sqrt{(-4y_1+4y_2)^2+(y_1-y_2)^2}=\sqrt{17(y_1-y_2)^2}=\sqrt{17}|y_1-y_2|](https://tex.z-dn.net/?f=AB%3D%5Csqrt%7B%28-4y_1%2B4y_2%29%5E2%2B%28y_1-y_2%29%5E2%7D%3D%5Csqrt%7B17%28y_1-y_2%29%5E2%7D%3D%5Csqrt%7B17%7D%7Cy_1-y_2%7C)
So, we can compute the distance between two points on the line just by knowing their y coordinates!
Now, the equation of a circle with center
and radius 5 is
![(x+1)^2+(y-2)^2=5^2](https://tex.z-dn.net/?f=%28x%2B1%29%5E2%2B%28y-2%29%5E2%3D5%5E2)
which we can reform as
![x^2 + y^2 + 2 x - 4 y - 20 = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%20y%5E2%20%2B%202%20x%20%20-%204%20y%20-%2020%20%3D%200)
The points of intersection between the circle and the line are given by the system between the two equations:
![\begin{cases}x^2 + y^2 + 2 x - 4 y - 20 = 0\\x+4y=0\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Dx%5E2%20%2B%20y%5E2%20%2B%202%20x%20%20-%204%20y%20-%2020%20%3D%200%5C%5Cx%2B4y%3D0%5Cend%7Bcases%7D)
From the second equation we can deduce
. Plugging this value in the first equation yields
![(-4y)^2 + y^2 + 2 (-4y) - 4 y - 20 = 0 \iff 17y^2-12y-20=0](https://tex.z-dn.net/?f=%28-4y%29%5E2%20%2B%20y%5E2%20%2B%202%20%28-4y%29%20%20-%204%20y%20-%2020%20%3D%200%20%5Ciff%2017y%5E2-12y-20%3D0)
Solving this equation for
yields
![y=\dfrac{12\pm\sqrt{144+1360}}{34}=\dfrac{12\pm\sqrt{1504}}{34}=\dfrac{12\pm\sqrt{16\cdot 94}}{34}=\dfrac{12\pm4\sqrt{94}}{34}=\dfrac{6\pm2\sqrt{94}}{17}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B12%5Cpm%5Csqrt%7B144%2B1360%7D%7D%7B34%7D%3D%5Cdfrac%7B12%5Cpm%5Csqrt%7B1504%7D%7D%7B34%7D%3D%5Cdfrac%7B12%5Cpm%5Csqrt%7B16%5Ccdot%2094%7D%7D%7B34%7D%3D%5Cdfrac%7B12%5Cpm4%5Csqrt%7B94%7D%7D%7B34%7D%3D%5Cdfrac%7B6%5Cpm2%5Csqrt%7B94%7D%7D%7B17%7D)
Now we have the two
values
![y_1=\dfrac{6+2\sqrt{94}}{17},\quad y_2=\dfrac{6-2\sqrt{94}}{17}](https://tex.z-dn.net/?f=y_1%3D%5Cdfrac%7B6%2B2%5Csqrt%7B94%7D%7D%7B17%7D%2C%5Cquad%20y_2%3D%5Cdfrac%7B6-2%5Csqrt%7B94%7D%7D%7B17%7D)
Which implies that the distance length of AB is
![AB=\sqrt{17}|y_1-y_2|=\sqrt{17}\cdot\dfrac{4\sqrt{94}}{17}=4\sqrt{\dfrac{94}{17}}](https://tex.z-dn.net/?f=AB%3D%5Csqrt%7B17%7D%7Cy_1-y_2%7C%3D%5Csqrt%7B17%7D%5Ccdot%5Cdfrac%7B4%5Csqrt%7B94%7D%7D%7B17%7D%3D4%5Csqrt%7B%5Cdfrac%7B94%7D%7B17%7D%7D)